Polityka handlu zagranicznego a konsumpcja indywidualna - Guzek, Marian (Wydział Prawa i Administracji UAM, 1967)
In the first part of the paper the author dwells on relations between the policy of foreign trade and the criterion of consumption maximization. Analyzing the consequences for the policy of foreign trade in case the criterion of consumption maximization prevails, the author comes to the conclusion the said criterion cannot constitute a sufficient premise for the rationalization of foreign trade. The structural consumption restrictions (and among them market disproportions) can be looked upon as an alternative of restricting the consumption fund. The planning body can thus consciously fix structural restrictions of market supplies — which the policy of foreign trade should strictly respect. It is only after taking into consideration — besides the criterion of consumption maximization — additional circumstances, such as the social costs sustained in conjunction with the disparity between the supply structure with the demand structure and the tendency of natural elimination of restrictions by the population itself (by means of individual contacts with foreign markets), that the author comes to the conclusion, that the market disproportions are irrational phenomena and as such, should be liquidated. The policy of foreign trade should be subordinated to that particular aim — as it still has at its disposal many ways and means of correcting the supply structure of market commodities. Consequently, the author proposes: — to treat the actual market prices as parameters for undertaking decisions in the field of current policy of foreign trade, — to take into consideration the disparity i market price relations in the Comecon countries.
The policy of foreign trade and individual consumption